Pengalaman Pasien Penyakit Ginjal Kronik yang Menjalani Hemodialisis dalam Mengikuti Asupan Diet dan Cairan: Studi Fenomenologi - Monika Blesinki; Dewi Elizadiani Suza; Mula Tarigan (Journal of Telenursing (JOTING), 2022)
This study aims to gather information about the life experiences of patients with chronic kidney disease undergoing hemodialysis in adhering to their diet and fluid intake. The method used is a phenomenological approach involving 15 patients undergoing hemodialysis at the H. Adam Malik General Hospital Medan selected by purposive sampling technique. Data collection was carried out using a qualitative approach in the form of in-depth interviews. Data were analyzed using the Colaizzi method. The results showed that there were seven themes regarding patient experience, namely; 1) changes in the patient's physiological condition; 2) expression of the patient's feelings regarding changes in health conditions; 3) the need to obtain support; 4) changes in meeting the nutritional needs of patients; 5) changes in fulfilling the patient's fluid needs; 6) the need to obtain information about treatment; and 7) patient's obstacles in following diet and fluid rules. In conclusion, each patient's experience in following diet and fluid intake is different. Keywords: Fluid Intake, Diet Intake, Hemodialysis